A case of repeat resection for recurrent pulmonary metastasis from sebaceous gland carcinoma - Sachi Kawagishi; Ryu Kanzaki; Seiji Taniguchi; Kenji Kimura; Toru Kimura; Hiroyuki Takabatake; Eiichi Morii; Masayoshi Inoue; Yasushi Shintani (Surgical Case Reports)
Abstract Background Sebaceous gland carcinoma (SGC) of the eyelid is an aggressive malignant eyelid tumor, and it can metastasize to the regional lymph nodes and distant organs. There have been only a few reported cases of patients who underwent pulmonary metastasectomy for metastatic SGC. We herein report a patient who underwent repeat pulmonary metastasectomies for recurrent pulmonary metastases from SGC. Case presentation Bilateral small pulmonary nodules were detected in a 59-year-old woman with a history of eyelid SGC. She underwent wide wedge resection of the left lower lobe, and the disease was diagnosed as pulmonary metastases from SGC. Six months after the first pulmonary resection, CT showed that the nodules of right S2 and S10 had increased in size, and three small nodules had newly appeared in the right lung. The patient therefore underwent six wide wedge resections of the right lung through thoracotomy. After that, she underwent pulmonary metastasectomy 2 times. Ninety months after the first pulmonary resection, the patient is doing well without disease. Conclusions Given that a long-term survival was ultimately achieved in the present case, repeat pulmonary metastasectomy may be beneficial for recurrent pulmonary metastasis from SGC.